Age and Sex-Associated Changes of Complement Activity and Complement Levels in a Healthy Caucasian Population - Gaya da Costa, Mariana; Poppelaars, Felix; van Kooten, Cees; Mollnes, Tom E.; Tedesco, Francesco; Würzner, Reinhard; Trouw, Leendert A.; Truedsson, Lennart; Daha, Mohamed R.; Roos, Anja; Seelen, Marc A. (Frontiers in Immunology, 2018)
Introduction: The complement system is essential for an adequate immune response. Much attention has been given to the role of complement in disease. However, to better understand complement in pathology, it is crucial to first analyze this system in different physiological conditions. The aim of the present study was therefore to investigate the inter-individual variation in complement activity and the influences of age and gender. Methods: Complement levels and functional activity were determined in 120 healthy volunteers, 60 women, 60 men, age range 20–69 year. Functional activity of the classical pathway (CP), alternative pathway (AP) and lectin pathway (LP) was measured in sera. In addition, levels of C1q, MBL, MASP-1, MASP-2, ficolin-2, ficolin-3, C2, C4, C3, C5, C6, C7, C8, C9, factor B, factor D, properdin, C1-inhibitor and C4b-binding protein, were determined. Age- and sex-related differences were evaluated. Results: Significant lower AP activity was found in females compared to males. Further analysis of the AP revealed lower C3 and properdin levels, while factor D concentrations were higher. For the LP, there was no influence of sex on the functional activity, but MBL and Ficolin-3 levels were significantly lower in females compared to males. In addition, there were no significant differences in CP activity or CP components. Lastly, females also had significant lower levels of the terminal components. At older ages, the CP and AP activity was enhanced, whereas there was a trend for an age-dependent decrease in LP activity. Moreover, C1-inhibitor, C5, C8 and C9 increased with age in contrast to a decrease of factor D and C3 levels. In-depth analysis of the functional activity assays revealed that LP activity was predominantly dependent on MBL and MASP-2 concentration, whereas CP activity relied on C2, C1-inhibitor and C5 levels. AP activity was strongly and directly associated with levels of C3, factor B and C5. Conclusion: This study demonstrated significant sex and age-related differences in complement levels and functionality in the healthy population. Therefore, age and gender analysis should be taken into consideration when discussing complement-related pathologies and subsequent complement-targeted therapies.